Evaluation of a new geothermal based multigenerational plant with primary outputs of hydrogen and ammonia - Yuksel, Yunus Emre; Ozturk, Murat; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Increasing environmental concerns and decreasing fossil fuel sources compel engineers and scientists to find resilient, clean, and inexpensive alternative energy options Recently, the usage of renewable power resources has risen, while the efficiency improvement studies have continued. To improve the efficiency of the plants, it is of great significance to recover and use the waste heat to generate other useful products. In this paper, a novel integrated energy plant utilizing a geothermal resource to produce hydrogen, ammonia, power, fresh water, hot water, heated air for drying, heating, and cooling is designed. Hydrogen, as an energy carrier, has become an attractive choice for energy systems in recent years due to its features like high energy content, clean, bountiful supply, non-toxic and high efficiency. Furthermore in this study, hydrogen beside electricity is selected to produce and stored in a hydrogen storage tank, and some amount of hydrogen is mixed with nitrogen to compound ammonia. In order to determine the irreversibilities occurring within the system and plant performance, energy and exergy analyses are then performed accordingly. In the design of the plant, each sub-system is integrated in a sensible manner, and the streams connecting sub-systems are enumerated. Then thermodynamic balance equations, in terms of mass, energy, entropy and exergy, are introduced for each unit of the plant. Based on the system inputs and outputs, the energy and exergy efficiencies of the entire integrated plant is found to be 58.68% and 54.73% with the base parameters. The second part of the analysis contains some parametric studies to reveal how some system parameters, which are the reference temperature, geothermal resource temperature and mass flow rate, and separator inlet pressure in the geothermal cycle, affect both energy and exergy efficiencies and hence the useful outputs. (c) 2021 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen; Ammonia; Geothermal energy; Multigeneration; Energy; Exergy; INTEGRATED-SYSTEM; Chemistry; Electrochemistry; Energy & Fuels